Resilience of gas interchangeability in hydrogen-blended integrated electricity and gas systems: A transient approach with dynamic gas composition tracking - Sheng Wang; Hongxun Hui; Pierluigi Siano (iEnergy, 2023)
Green hydrogen can be produced by consuming surplus renewable generations. It can be injected into the natural gas networks, accelerating the decarbonization of energy systems. However, with the fluctuation of renewable energies, the gas composition in the gas network may change dramatically as the hydrogen injection fluctuates. The gas interchangeability may be adversely affected. To investigate the ability to defend the fluctuated hydrogen injection, this paper proposes a gas interchangeability resilience evaluation method for hydrogen-blended integrated electricity and gas systems (H-IEGS). First, gas interchangeability resilience is defined by proposing several novel metrics. Then, A two-stage gas interchangeability management scheme is proposed to accommodate the hydrogen injections. The steady-state optimal electricity and hydrogen-gas energy flow technique is performed first to obtain the desired operating state of the H-IEGS. Then, the dynamic gas composition tracking is implemented to calculate the real-time traveling of hydrogen contents in the gas network, and evaluate the time-varying gas interchangeability metrics. Moreover, to improve the computation efficiency, a self-adaptive linearization technique is proposed and embedded in the solution process of discretized partial derivative equations. Finally, an IEEE 24 bus reliability test system and Belgium natural gas system are used to validate the proposed method.